Republic Kazakhstan Cooperation with the European Union - T K Tokaev (Vestnik RUDN. International Relations, 2010)
The article is dedicated to the analysis of Kazakhstan foreign policy towards the European Union. Kazakhstan considers itself as a leading regional state in the Central Asia. Kazakhstan suggests its European partners a wide set of measures to cooperate and transfer the bilateral relations with the EU member countries to the plane of strategic partnership.